2016
DOI: 10.1080/17441692.2016.1178318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between population mobility and HIV risk: Evidence from Tanzania

Abstract: Migration and population mobility has long been regarded as an important structural driver of HIV. Following initial concerns regarding the spatial spread of the disease, mobile populations are viewed to engage in higher levels of risky sexual behaviours than non-mobile groups. However, beyond the case studies of mineworkers and truck drivers, the statistical evidence is inconclusive, suggesting that the relationship between mobility and risk is not well understood. This study investigated how engaging in spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As important as mobility may be to an individual's economic survival, it has also been associated with interrupting lifestyles, access to healthcare services and elevating risk profiles of those affected [14,29,30]. In this study we found that mobility was associated with high risk sexual behaviour that exposed individuals to HIV infections.…”
Section: Discussionmentioning
confidence: 57%
“…As important as mobility may be to an individual's economic survival, it has also been associated with interrupting lifestyles, access to healthcare services and elevating risk profiles of those affected [14,29,30]. In this study we found that mobility was associated with high risk sexual behaviour that exposed individuals to HIV infections.…”
Section: Discussionmentioning
confidence: 57%
“…Improving the resilience of affected populations against the associated health risks, might be considered an integral part of such development. Moreover, as the population in these areas is likely to be highly mobile [41,42], effective prevention for young adults in high-prevalence areas may not only affect the local HIV epidemics, but also the wider epidemic. Ultimately, our results demonstrate that the decade-old mantra of "know your epidemic, know your response" [43] is still highly relevant for SSA.…”
Section: Discussionmentioning
confidence: 99%
“…An evidence from Tanzania indicated that patterns and conditions of mobile population in relation to their requirements of each different economic activity influenced the nature of relationships that mobile groups have, how and where local sexual networks are accessed, and the practicalities of having sex. The authors pointed that this trend has further implications for condom use [ 39 ]. Another study among the key populations in Tanzania indicated that the long-truck drivers were potentially at risk of engaging in higher risk sex (not using condoms during heterosexual anal sex) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%